(untitled) - Join, Jean-Lambert; Bonnier, Julien; Clément, Alain; Fritz, Bertrand (Comptes Rendus. Géoscience, 2025)
This study examines groundwater flow paths and geochemical processes in the Piton des Neiges volcano on Reunion Island. Using data from the Salazie Amont tunnel, bored at a depth of 1000 m under the planèze of Plaine des Fougères, we characterise groundwater composition and weathering processes in volcanic terrains. The study area features high permeability in shallow lava flows, enabling deep water infiltration, but also demonstrates a decrease in permeability with increasing depth due to mineral precipitation of secondary phases, mainly clays.Reactive transport in the vadose and phreatic zones was modelled with KIRMAT, a geochemical code simulating water–rock interactions. Initial rainwater undergoes chemical changes while percolating through volcanic rock, increasing in pH and mineral content. In the phreatic zone, simulation results suggested magmatic CO$_{2}$ input, impacting water pH and mineral composition. The model captured observed mineral trends effectively, predicting significant secondary mineral formation at depth, particularly clay minerals. Results illustrate how mineralisation reduces permeability in volcanic formations over time, progressively creating an impermeable barrier in the volcano’s core. This research provides insights into the long-term evolution of groundwater systems in shield volcanoes, contributing to the understanding of aquifer dynamics and material flow in volcanic environments.